مسؤولية الناقل الجوي في عقد نقل الركاب على ضوء الاتفاقيات الدولية والتشريع العماني - محمد بن راشد بن أحمد المخمري
This study is aimed to declare that the Air Carrier is responsible to carry passengers based on the International Agreements and the Omani Law. The researcher thinks that this kind of study has theoretical and practical importance due to the importance of Air Carrier recently in the economic life. Also, it is considered as one of the effective factor in trading, products marketing and countries' improvement. The problematic point here is there are many different points of view regarding the basic Law towards the responsibility of the Air Carrier in carrying passengers. The researcher has used Information analysis technique to reach the study goals and get the point which will be helpful for all. The technique used to analyze Air Carrier's definition, features and its effects. Also, to declare the responsibility Air Carrier regarding the International Agreements and the Omani Law with a reference to the Islamic view. Moreover, there are attempts to avoid putting air carrier's responsibility in passengers' contract which may have effects towards passengers as well. Finally, this study reached got results such as, Warso Agreement (1929) and its modified protocols. This agreement showed the differences and the contrast among many legal systems which control the responsibility of Air Carrier. Also, it doesn't achieve the aimed balance between passengers' benefits and Air Carrier's benefits when all its legal texts stand with Air Carriers rather than passengers and that's why this agreement didn't succeeded to unite air transportation laws. Moreover, there are so many agreements has been signed and ended up with Monterial Agreement (1999) and started using it on 4/11/2003 as the main agreement of air transportation and Oman has joined it on 25/6/2006.